Digital strategies and non-conventional sources of innovation: Analysis of causal relationships using interpretive structural modeling - Farinha, I. M.; Ferreira, F. A. F.; Ferreira, N. C. M. Q. F.; Edwin, G.; Daim, T. (Technology in Society, 2025)
Digitalization appears to have sped up in recent years, and many companies have seen their business models changed irreversibly. In this context, small and medium-sized enterprises (SMEs) should adopt different business approaches that help these firms thrive and maintain and/or create sustainable competitive advantages. SMEs’ specificities can present obstacles to this adaptation process, yet these challenges may turn out to be the greatest allies of these companies if they stimulate swift, quick transformations. This study sought to develop an analysis system that identifies appropriate digital strategies and non-conventional sources of innovation, which can thus promote sustainable SME innovation. To achieve this goal, the research applied constructivist logic and combined cognitive mapping and interpretive structural modeling (ISM) to identify and analyze key variables and their respective cause-andeffect relationships that enhance successful innovation processes. A panel was formed of experts with professional experience and knowledge in this field, whose participation provided added value to the study’s decision-making process through the incorporation of objective and subjective variables. The results and the analysis system’s potential practical applications were validated in a final consolidation session with an expert from Portugal’s Agência Nacional de Inovação (i.e., National Innovation Agency). Theoretical and practical contributions are also discussed, as well as the limitations of the selected methodologies.